Metastases of kidney cancer into the thyroid gland (сlinical observation) - N. A. Ognerubov; S. V. Barsukov; V. L. Chang; G. E. Gumareva; T. S. Antipova (Опухоли головы и шеи, 2017)
The article presents a literature review considering epidemiological aspects of secondary cancer of the thyroid gland. The authors’ clinical observation of renal cell carcinoma metastasis into the thyroid gland with tumor thrombus of the internal jugular vein is described. The authors emphasize the necessity of complex diagnostics and treatment of renal cell carcinoma.